2017
DOI: 10.1371/journal.pone.0181368
|View full text |Cite
|
Sign up to set email alerts
|

A self-affirmation exercise does not improve intentions to vaccinate among parents with negative vaccine attitudes (and may decrease intentions to vaccinate)

Abstract: Two studies investigated the effectiveness of a self-affirmation exercise on vaccine safety beliefs and intent to vaccinate future children. In Study 1, a sample of 585 parents with at least one child under the age of 18 in the home participated through Amazon’s MTurk. Participants were randomly assigned to one of four conditions in a 2 x 2 design. Participants read either correcting information refuting a link between the measles, mumps, and rubella (MMR) vaccine and autism or a control passage about bird fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 32 publications
0
13
0
2
Order By: Relevance
“…This study supports evidence from previous findings, showing that vaccine-hesitant parents follow a more thorough deliberation process by carefully weighing the pros, cons, alternatives and consequences of accepting or refusing vaccination, compared to acceptors [ 36 , 49 ]. There is a relatively small body of literature that emphasizes the deliberation of values in regard to vaccination decision-making [ 38 , 40 , 53 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study supports evidence from previous findings, showing that vaccine-hesitant parents follow a more thorough deliberation process by carefully weighing the pros, cons, alternatives and consequences of accepting or refusing vaccination, compared to acceptors [ 36 , 49 ]. There is a relatively small body of literature that emphasizes the deliberation of values in regard to vaccination decision-making [ 38 , 40 , 53 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…flu vaccine causes the flu [10] and measles, mumps and rubella (MMR) vaccine causes autism [12]) had no effect on vaccine intention or attitude, respectively. A 2017 study on the effect of self-affirmation exercises found it to be ineffective or even detrimental when correcting information regarding vaccine safety was not jointly provided [11]. To this effect, recent work by Hornsey et al [21, 34] shed new light into the roots of antivaccination attitudes while also proposing a new model for promoting vaccine acceptance that seems promising.…”
Section: Discussionmentioning
confidence: 99%
“…One method that has been shown to increase the feeling of control is self-affirmation through the reminder of values important to the individual 156 which also reduced memory of misinformation in another study 157 . However, a contrary study shows that the self-affirmation procedure is ineffective in increasing the intention to vaccinate in people with a negative vaccination attitude 158 . Similarly, another strategy which warrants further investigation are attempts try to increase the likelihood of adherence to safety guidelines and vaccinations by emphasising positive consequences of these behaviours 27 .…”
Section: Limitations and Future Researchmentioning
confidence: 96%